Answer:
(d) Yes. (3x + 3) - (2x + 2y + 4)
Step-by-step explanation:
The first answer choice results in a monomial, -2y
The second answer choice results in a binomial, x -y
The third answer choice is proved wrong by the fourth answer choice.
The fourth answer choice results in x -2y -1, a trinomial.
Answer:
Solve for y in the second equation
Step-by-step explanation:
We assume your system is ...
Dividing <em>the </em><em>second equation</em> by 3 gives ...
-3x +y = 1
so an expression for y without fractions can be found by <em>solving for y</em>, that is, by adding 3x:
y = 3x +1
_____
<em>Comment on alternate solution</em>
We'd be tempted to solve the first equation for -9x and substitute for that.
-9x = 10 -4y
(10 -4y) +3y = 3 . . . . . substitute for -9x
-y = -7 . . . . . . . . . . . . . simplify, subtract 10
y = 7 . . . . . . . . . . . . . . multiply by -1
The answer is “A” hope I helped
Answer:
$3142.86
Step-by-step explanation:
3300 --> 105%
x --> 100%
criss cross method
x=330000/105
x=3142.86